Ajustes autonômicos cardíacos frente ao exercício físico e mudança postural em indivíduos com doença de Parkinson - Mello, Roberta Lorena Moreira de (Universidade Federal de São Carlos, 2019)
Parkinson's disease (PD) involves damage to dopaminergic neurons of the nigrostriatal pathway. The dysregulation of cardiovascular autonomic modulation is one of the non-motor impairment described in this disease. Adjustments of cardiac autonomic modulation can be tested by different stressors such as exercise and postural changes and can be verified by the behavior of a tool known as heart rate variability (HRV). Considering the importance of neurocardial autonomic control in the face of the diversity of adjustments needed and the different demands imposed on daily life added to the impairment of PD, it is pertinent to investigate autonomic adjustments in this population. The aim of this study was to evaluate the adjustments of cardiac autonomic modulation against stressors such as exercise and postural change in individuals with PD. Twenty individuals were divided into two groups. Ten individuals with PD (GDP, n = 10) and ten healthy volunteers (CG, N = 10) matched for age and gender. For the analyzes related to the autonomic modulation of the heart rate (HR) in relation to the postural change (GDP only) and exercise, HR signals and RR intervals were obtained by means of a PolarS810i telemetry system and the evaluation of stationary sections of the signal containing 256 points in supine, lying down and standing conditions, as well as in sitting rest conditions, during submaximal exercise and recovery after exercise. There was no significant difference for HRV indices regarding postural change in individuals with PD. For intragroup analyzes at rest there was a statistical difference in the RMMSD, SD1, RRtri, TINN, SD2 and STDRR indices, with lower values for SD. There was no statistically significant intra-group difference in HRV analysis at the 6MWT. At recovery, there was intragroup difference in mean HR, RR average, LF / HF, SD2 / SD1, LF and HF. In the intragroup analysis, individuals with PD had a reduction in HRV indices (DMSR, SD1, RRtri, TINN, SD2 and STDRR) at rest for the 6MWT and an increase in the same indices at recovery. CONCLUSION: We concluded that individuals with PD present autonomic adjustment in relation to exercise stimulus (rest x 6MWT x recovery), however, there were no changes in HRV in postural change, and individuals with PD showed a delay in recovering in the indices of postural change. HRV when compared to healthy ones.
Cardiac autonomic adjustments in physical exercise and postural change in Parkinson disease individuals
Keywords: Doença de Parkinson; Modulação autonômica; Teste de caminhada; Parkinson's disease; Autonomic modulation; Walking test; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL